2012
DOI: 10.1101/gad.193409.112
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicle clustering requires a distinct MIG-10/Lamellipodin isoform and ABI-1 downstream from Netrin

Abstract: The chemotrophic factor Netrin can simultaneously instruct different neurodevelopmental programs in individual neurons in vivo. How neurons correctly interpret the Netrin signal and undergo the appropriate neurodevelopmental response is not understood. Here we identify MIG-10 isoforms as critical determinants of individual cellular responses to Netrin. We determined that distinct MIG-10 isoforms, varying only in their N-terminal motifs, can localize to specific subcellular domains and are differentially requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 75 publications
4
46
0
Order By: Relevance
“…Two other groups working concurrently have now also shown that MIG-10 and ABI-1 interact (Quinn and Xu, 2012; Stavoe et al, 2012). Our results demonstrate that MIG-10A and ABI-1 interact in a yeast two-hybrid system, and that either MIG-10A or MIG-10B co-immunoprecipitate with ABI-1 in insect cells, suggesting that these proteins physically interact.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Two other groups working concurrently have now also shown that MIG-10 and ABI-1 interact (Quinn and Xu, 2012; Stavoe et al, 2012). Our results demonstrate that MIG-10A and ABI-1 interact in a yeast two-hybrid system, and that either MIG-10A or MIG-10B co-immunoprecipitate with ABI-1 in insect cells, suggesting that these proteins physically interact.…”
Section: Discussionmentioning
confidence: 95%
“…Three MIG-10 isoforms are predicted, MIG-10A, B, and C (Fig 1). Cell autonomous expression of MIG-10A has been shown to be sufficient to rescue some mig-10(ct41) axon outgrowth defects (Chang et al, 2006; Quinn et al, 2006; Quinn et al, 2008), while cell autonomous expression of MIG-10B is sufficient to rescue defects in synaptic vesicle clustering observed in mig-10(ct41) animals (Stavoe et al, 2012). MIG-10C has not been shown to be required for rescue of any mutant phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that F-actin functions within or near synaptic vesicle pools. 17,43,62 At the Drosophila NMJ, actin is observed as distinct puncta in synaptic boutons. 63 Similarly, several proteomic studies have identified actin as a component of the synaptic vesicle and active zone proteomes.…”
Section: F-actin Is Required For Proper Development Of the Presynaptimentioning
confidence: 99%
“…17,62 Interestingly, the RacGEF involved in this pathway, CED-5/DOCK180, while required for vesicle clustering, is not required for proper localization of active zone proteins to presynaptic sites. These findings suggest that active zone assembly and synaptic vesicle clustering are instructed by two different signaling pathways downstream from Netrin.…”
Section: F-actin Is Required For Proper Development Of the Presynaptimentioning
confidence: 99%